Skeletal Muscle Deoxygenation in 11-13-year-old Children Swimmers During Arm and Leg Ergometry - Aura Mažuolytė–Binderienė; Loreta Stasiulė (Baltic Journal of Sport and Health Sciences)
Background: This study extends the current knowledge on muscle deoxygenation during arm and leg ergometry in preadolescent swimmers. We aimed to compare the deoxygenation of legs and arms muscles during maximal incremental legs and arms exercises on the cycle ergometer (CE) and arm crank ergometer (ACE) in preadolescent swimmers.